The effect of thiamine deficiency on inflammation, oxidative stress and cellular migration in an experimental model of sepsis - de Andrade, José Antenor Araújo (BioMed Central, 2014)
BACKGROUND: Sepsis is a prevalent condition in critically ill patients and may be associated with thiamine deficiency (TD). The aim of this study was to evaluate the effect of TD on inflammation, oxidative stress and cellular recruitment in a sepsis model. METHODS: The experimental sepsis model, cecal ligation and puncture (CLP), was utilized on mice in comparison with a sham procedure. The following four groups were compared against each other: SHAM with AIN93G complete chow, SHAM with thiamine deficient (TD) chow, CLP with AIN93G complete chow, and CLP with TD chow. Thiamine pyrophosphate (TPP) blood concentrations were determined, and blood and peritoneal fluid were evaluated for differences in TNF-alpha, IL-1, IL-6, KC and MCP-1/CCL2 levels. In addition, the levels of 4-HNE adducts in liver proteins were evaluated by Western Blot. RESULTS: The mean TPP blood concentration from the mice fed with the complete chow was 303.3 ± 42.6 nmol/L, and TD occurred within 10 days. TNF-α and MCP-1 concentrations in the peritoneal fluid were significantly greater in the CLP with TD chow group when compared with the other groups. The blood IL-1β level, however, was lower in the CLP with TD chow group. Liver 4-HNE levels were highest in the TD chow groups. Blood mononuclear cell numbers, as well as peritoneal total leukocyte, mononuclear cell and neutrophil numbers were greater in the CLP with TD chow group. Peritoneal bacterial colony forming units (CFU) were significantly lower in the CLP with TD chow group. CONCLUSION: TD was associated with greater bacterial clearance, oxidative stress and inflammatory response changes.